25‐Hydroxyvitamin D and Cardiovascular Disease in Patients With Systemic Lupus Erythematosus: Data From a Large International Inception Cohort. Issue 8 (August 2014) - Lertratanakul, Apinya; Wu, Peggy; Dyer, Alan; Urowitz, Murray; Gladman, Dafna; Fortin, Paul; Bae, Sang‐Cheol; Gordon, Caroline; Clarke, Ann; Bernatsky, Sasha; Hanly, John G.; Isenberg, David; et al.
<x xml:space="preserve">Abstract</x> Objective An association between 25‐hydroxyvitamin D (25[OH]D; vitamin D) deficiency and increased cardiovascular (CV) risk factors and CV disease (CVD) has been shown in general population studies. Vitamin D deficiency has been noted in systemic lupus erythematosus (SLE), and CVD is a major cause of morbidity and mortality in SLE. The objectives of this study were to estimate the associations of 25(OH)D levels with CV risk factors and to determine whether low baseline 25(OH)D levels predict future CV events in patients participating in an international inception cohort. Methods Data were collected on 890 participants, including demographics, SLE activity and damage assessments, CV risk factors and events, medications, laboratory assessments of 25(OH)D levels, and inflammatory markers. Multiple logistic and Cox regressions were used to estimate the associations of baseline 25(OH)D levels with baseline CV risk factors and CVD events. The models were adjusted for age, sex, race, season, and country, with and without body mass index. Results Patients in the higher quartiles of 25(OH)D were less likely to have hypertension and hyperlipidemia and were more likely to have lower C‐reactive protein levels and lower Systemic Lupus Erythematosus Disease Activity Index 2000 scores at baseline when compared with the first quartile. Vitamin D levels were not independently associated with CVD event incidence; however, hazard ratios for CVD event incidence decreased with successively higher quartiles. Conclusion Lower baseline 25(OH)D levels are associated with higher risk for CV risk factors and more active SLE at baseline. There may be a trend toward a lower likelihood of CVD events in those with higher baseline 25(OH)D levels.